Simultaneous determination of cadmium, lead and copper in chocolate samples by square wave anodic stripping voltammetry. Issue 3 (4th March 2021) - Silva, Larissa Pinto; Campos, Náira Da Silva; Lisboa, Thalles Pedrosa; de Faria, Lucas Vinícius; Matos, Maria Auxiliadora Costa; Matos, Renato Camargo; de Sousa, Rafael Arromba
ABSTRACT: In this work, an effective and simple method is proposed for the simultaneous determination of cadmium, lead and copper in chocolate samples by Square Wave Anodic Stripping Voltammetry (SWASV). An ultrasonic bath was used for the extraction of cadmium, lead and copper from fourteen chocolate samples using HNO3 solution (7 mol L −1 ). The electrochemical system consisted of a cell with three electrodes and HCl solution (10 mmol L −1 ) as the supporting electrolyte. An efficient extraction of the metals (~100%) was attained after 1 h of ultrasonic pre-treatment. Quantitative analysis was carried out by the standard addition method. Good linearity, precision and accuracy were obtained in the range of concentrations examined. The accuracy was evaluated by means of a reference sample of spiked skim milk powder (BCR 151) to prove the reliability of the method. Detection limits (LOD) of 0.089, 0.059 and 0.018 µg g −1 were found for cadmium, copper and lead, respectively, in the chocolate samples. Concentrations in chocolate samples were 4.30–138 µg g −1 for Cu and 0.83–27.9 µg g −1 for Pb, with no significant Cd. The simultaneous determination brings advantages to other methods already reported for chocolate analysis and the samples preparation proposed avoids the traditional sample mineralization step. These characteristics show this new method is especially attractive for case studies and routine analysis. Graphical Abstract: